Tattered scripts: Stories about the transmission of trauma across generations. (May 2016) - Fewell, Judith
Abstract: This paper explores how our families' unnarrated and unspeakable stories – the ghostly hauntings of our ancestors' unremembered past – exert their influence across generations. Drawing upon cultural, historical and psychoanalytic accounts of these hauntings, I seek to offer ways of making sense of these disturbing familial and personal experiences.